Ocular Findings in Patients with Chronic Kidney Disease: A Hospital Based Cross-Sectional Study - Godar, Srijana Thapa; Khattri, Jai Bahadur; Maskey, Abhishek (Journal of Nepalgunj Medical College, 2025)
Introduction: Chronic kidney disease affects every organ system including the eye. Aims: To study the prevalence of anterior and posterior segment ocular findings in patients with chronic kidney disease. Methods: This was a hospital based cross-sectional study conducted among 86 patients of chronic kidney disease of all ages and either gender from June 2024 to November 2024. Standard proforma was used to collect socio-demographic and clinical variables of the patients. Detailed ocular examination including fundus evaluation was done and diabetic retinopathy and hypertensive retinopathy was graded according to the Early Treatment of Diabetic Retinopathy Study (ETDRS) classification and Keith-Wegener-Barker classification respectively. Results: The mean age of the study sample was 60.73 (±14.80) years with male preponderance (62.79%). The commonest cause of chronic kidney disease was both (diabetes and hypertension) (45.35%) followed by hypertension (40.70%). The most prevalent anterior segment ocular finding was pingecula (60.47%) followed by eyelid edema (36.05%), cataract (31.40%) and conjunctival pallor (27.91%). Retinopathy (72.09%) was the most prevalent posterior segment ocular finding. Among retinopathy, the prevalence of hypertensive retinopathy, diabetic retinopathy and both retinopathy (hypertensive and diabetic retinopathy) was 51.61%, 30.64% and 17.74% respectively. The prevalence of vitreous haemorrhage, tractional retinal detachment and maculopathy was 1.16%, 2.33% and 9.67% respectively. Conclusion: There is high prevalence of ocular findings in the chronic kidney disease. Regular ocular examination is mandatory for early detection and treatment to prevent ocular morbidity and blindness in chronic kidney disease.